Ibuanyidanda and the Principle of Non-Contradiction: A Logico-Metaphysica Discourse of Asouzu’s Complementary - Uzoigwe, Elias Ifeanyi E. (PREDESTINASI, 2020)
Ibuanyidanda and The Principle of Non-Contradiction aims at instantiating the claims of Asouzu’s Complementary Reflection that whatever exists serves as a missing link of reality. Reality has been construed within a bifurcating frame of mind, a project that was characterized by the elitist mindset of Plato and was further espoused in Aristotle’s philosophy of essence. For Aristotle, the wise is destined to rule the unwise. This divisive mentality permeates the entire Western culture. Unfortunately, Placid Tempels made some African scholars to erroneously believe and argue that the Western understanding of being is static, while that of Africa is dynamic. This anomaly, among other things, is what Ibuanyidanda as a philosophy and a method of doing philosophy sets out to address. Ibuanyidanda ontology contends that reality can be better understood from the complementary point of view. The principle of non-contradiction championed by Aristotle and the Western scholars sees the opposite of being as non-being, but Asouzu’s complementary reflection sees the opposite of being as to be alone (ka so mu di). This work holds that ibuanyidanda complementary reflection is capable of handling the problems of contradiction that are apparent in the Western mode of philosophising. Opposites do not contradict themselves, they complement each other. Ibuanyidanda philosophy and its position are contrary to the views of Aristotle’s metaphysics and open to sight ontological updating - a good recipe for the advancement of 21st-century philosophizing. Analytic, textual, contextual, and historical methods are employed in this work.